Konsentrasi dan Frekuensi Penyemprotan Pupuk Daun untuk Meningkatkan Pertumbuhan Bibit Protium Javanicum - M. Taufiqurrahman; A. Nadirman Kahfi; Hengki Siahaan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Taufiqurrahman M, Kahfi AN, Siahaan H. 2020. Concentration and frequency of spraying foliar fertilizer to increase the growth of Protium javanicum seedlings. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Kayu bawang (Protium javanicum, Burm. F) is a type of tree seed that has many advantages and benefits. One of the problems faced in cultivating kayu bawang seedlings is producing seeds with good growth. The aim of this research was to examined the effect of concentration and frequency of spraying foliar fertilizer on the growth of kayu bawang seedlings. The research was conducted at the nursery of Palembang Forestry and Inveronmental Research and Development Center. This study used foliar fertilizer at doses 0, 5, 10, 15 mL/L of water with the main content of nitrogen and potassium. Data collection was carried out by observing 216 seeds in polybags. The results were showed that all levels of fertilizer concentration and frequency of foliar fertilizer spray had no significant effect on all observed parameters, but the concentration of 5 mL/L tended to be better than other concentrations and the frequency of spraying once every 2 weeks tended to be better than other frequency, and the interaction between foliar fertilizer with a concentration of 5 mL/L and a frequency of spraying once every 2 weeks tended to be better than other interactions. From the research that has been done, it is concluded that the best dose of foliar fertilizer to increase kayu bawang seedling growth is with a concentration of 5 mL/L with a frequency of spraying every 2 weeks.